HUBUNGAN PEMBELAJARAN SENI MUSIK DENGAN PERKEMBANGAN KEMAMPUAN BERPIKIR PESERTA DIDIK DI SEKOLAH DASAR - Kenza Efrillia, Putri; Winarni, Wiwin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Music education plays an important role in supporting the cognitive, affective, and psychomotor development of elementary school students. This study aims to analyze the contribution of music education to the development of students' thinking skills and to identify other aspects of development that can be supported through musical activities. This research employs a literature review method with a qualitative approach, drawing from journals, books, and relevant policy documents. The findings indicate that music education not only enhances artistic skills but also plays a role in shaping character, strengthening emotional intelligence, and developing critical thinking and problem-solving abilities. Music can influence mood, improve concentration, and strengthen memory and motor coordination. Art education, as emphasized by Ki Hajar Dewantara (in Bastom, 1993: 20), is an important element in the formation of a child's personality. Therefore, music education in elementary schools should be designed to be enjoyable, contextual, and appropriate for the students' developmental stage to create meaningful and comprehensive learning.])